Optimalisasi Strategi Pemasaran Melalui Platform Digital untuk Meningkatkan Penjualan Anyaman Bambu di Desa Kalipucang Kulon - Ansori, Miswan; Nur Maulidia, Rizka; Ramadhan Pujisantoso, Rahmat; Putri Ningsih, Nia; Ilham, Mohammad; Dewi Saputri, Oktaviana; Sholikhati Ikmah, Ika; Irfana, Naila; Rizky Amalia, Ratna; Rosidah, Ida; Eka Fitri Nor Faizah, Natasya; Abdulloh Yusuf, Ahmad; Dwi Arini, Rina; Naufal Rif’at, Dhany; Putri Anjar Sari, Laila; Sholihatussifa, Nailis (Profetik: Jurnal Pengabdian Masyarakat, 2024)
In today's digital era, digital-based marketing strategies have become crucial for the success of Micro, Small, and Medium Enterprises (MSMEs) in enhancing competitiveness and expanding market reach. This community service program was conducted by the UNISNU XVII KKN Team in collaboration with the Fahri Parcel MSME in Kalipucang Kulon Village, Welahan District, Jepara Regency. The program aimed to optimize marketing strategies through digital platforms to increase the sales of bamboo weaving products. The methods used in this program included observation, mentoring, and intensive training focused on enhancing brand identity, creating and managing accounts on digital platforms (such as Shopee and Instagram), and developing skills in digital content creation. The results of this program showed a significant increase in brand recognition, market reach, and sales of Fahri Parcel's products. In conclusion, optimizing marketing strategies through digital platforms proved effective in improving the performance of the partner MSME. The active participation of the partner in every stage of the program also ensured the sustainability of the implemented strategies. This program not only provided direct benefits to the Fahri Parcel MSME but also enriched the practical experience of the service team in applying digital marketing knowledge. Thus, this program contributes to strengthening the competitiveness of MSMEs in the digital era.